Answer:
3) f(x) = 3(x + 2)^2 - 1.
Step-by-step explanation:
f(x) = 3x² + 12x +11
f(x) = 3(x^2 + 4x) + 11 Completing the square:
f(x) = 3[(x + 2)^2 - 4] + 11
f(x) = 3(x + 2)^2 -+3*-4 + 11
f(x) = 3(x + 2)^2 - 12 + 11
f(x) = 3(x + 2)^2 - 1.
Answer:
one
Step-by-step explanation:
i have no idea what kind of test ur taking my guy but have fun
Answer:
M, N, O
Step-by-step explanation:
This line contains the letter "M"
Answer:
11
13
15
23
Step-by-step explanation:
you substitute each x value in the table with the x in the equation
f(x)= 2x+13
f(x)= 2(-1)+13 .... repeat for each
If you have several different sized pizzas, you can compare their areas. So the area of a pizza is the length of the crust (circumference) divided by two times the distance from the edge to the middle (radius). Mathematicians use a special number called pi to calculate the circumference of a circle.